2016
DOI: 10.2166/wst.2016.331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple wastewater feedings on the efficiency of nutrient removal in an IFAS-MBSBBR: number of feedings vs. efficiency of nutrient removal

Abstract: This article presents the results of research into the influence of one, two and three wastewater feedings in a cycle on efficiency and performance of combined biological nitrogen and phosphorus removal in an integrated fixed-film activated sludge and moving-bed sequencing batch biofilm reactor (IFAS-MBSBBR). The experiment lasted 158 days and was conducted in two laboratory models of the IFAS-MBSBBR with an active volume of 28 L. It was found that along with an increase in the number of wastewater feedings, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The highest efficiency of the denitrification process (91.1 ± 1.8%) was achieved in series A3, probably due to the introduction of multiple feeding, which allows for better use of the organic compounds by the biomass present in the reactor. Our previous studies [ 15 ] have shown that the number of feedings in the cycle has a significant impact on the effectiveness of the denitrification process in the IFAS-MBSBBR system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The highest efficiency of the denitrification process (91.1 ± 1.8%) was achieved in series A3, probably due to the introduction of multiple feeding, which allows for better use of the organic compounds by the biomass present in the reactor. Our previous studies [ 15 ] have shown that the number of feedings in the cycle has a significant impact on the effectiveness of the denitrification process in the IFAS-MBSBBR system.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the similar physiology of PAO and GAO (organic substance uptake in anaerobic conditions, ability to respire in the presence of nitrate or nitrite), the overlap of ecological niches of the two groups is high, and therefore there should be a tendency for ruling out one of the two groups. The two groups coexist in most of the full scale enhanced biological phosphorus removal plants [ 22 , 23 ] and laboratory systems [ 10 , 15 ]. They are also found together in systems focused on denitrifying dephosphatation [ 15 ] and in the system presented in the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations